The Euro-dollar market - Clendenning, E. Wayne (Oxford : Clarendon Press, 1970)
This book attempted to highlights the dangers and weakness of the Euro-dollar market and its impact on national economies and the international financial system. It also tries to establish the theoretical underpinnings of the market.
Includes index
Bibliography: p. [231]-232.
usc 23/04/18
Loans
Keywords: Euro-dollar market